Lithium ion secondary battery

By adjusting the content of magnesium in silicon carbon materials and the ratio of cyclic carbonate and fluorine-containing lithium salts in the electrolyte, a stable SEI film is formed, which solves the particle powdering and fall off caused by volume expansion of silicon material in lithium-ion batteries. The problem is that the battery has improved the high-temperature storage and low-temperature circulation performance.

CN119400931APending Publication Date: 2025-02-07ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568502.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The volume of silicon material in lithium-ion batteries expands and shrinks greatly during charging and discharging, resulting in particles powdering and falling off, affecting the cycle stability of the battery.

Method used

By adjusting the content of magnesium in silicon carbon materials, the mass proportion of cyclic carbonate and fluorine-containing lithium salts in the electrolyte, they satisfy the specific relationship, and forming a stable SEI film to inhibit the volume expansion of the negative electrode and the particle powdering.

Benefits of technology

It improves the battery's high-temperature storage performance and low-temperature circulation performance, enhances the adhesion between the diaphragm and the pole plate, and improves the battery's cycle stability and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400931A_ABST
    Figure CN119400931A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium ion secondary battery. The battery comprises a positive plate, a negative plate and electrolyte, the negative plate comprises a negative current collector and a negative active material layer arranged on at least one side surface of the negative current collector, the negative active material layer comprises a negative active material, and the negative active material comprises a silicon carbon material; the silicon-carbon material comprises Mg element, and the content of the Mg element is recorded as Zppm; the electrolyte comprises a first solvent, and the first solvent comprises cyclic carbonate; based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate is E%; the electrolyte comprises fluorine-containing lithium salt, and based on the total mass of the electrolyte, the mass ratio of the fluorine-containing lithium salt is N%; z, E and N meet the condition that (E + N) / Z is more than or equal to 0.2 and less than or equal to 10, and the high-temperature storage performance and low-temperature cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] Lithium-ion batteries are rechargeable batteries that rely mainly on the movement of lithium ions between the positive and negative electrodes to work. Due to their many advantages such as high energy density, long life, and low self-discharge rate, lithium-ion batteries are currently used in a variety of scenarios. In order to further improve the energy density of lithium-ion batteries and solve people's "mileage anxiety" about energy storage devices, silicon materials have entered the researchers' perspective as an ideal negative electrode active material. The theoretical specific capacity of silicon materials far exceeds that of traditional graphite, which means that it can store more electrical energy and significantly improve the energy density of the battery. However, the volume expansion and contraction of silicon materials during the charging and discharging process is large, which can easily lead to particle pulverization and shedding, thereby affecting the cycle stability of the battery. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion secondary battery. By adjusting the content of magnesium in the silicon-carbon material, the mass proportion of cyclic carbonate and fluorine-containing lithium salt in the electrolyte, when the three satisfy a specific relationship, the high-temperature storage performance and low-temperature cycle performance of the battery can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material; the silicon-carbon material comprises a Mg element, and the content of the Mg element is recorded as Zppm;

[0006] The electrolyte includes a first solvent, and the first solvent includes a cyclic carbonate; the mass proportion of the cyclic carbonate is recorded as E% based on the total mass of the electrolyte;

[0007] The electrolyte includes a fluorine-containing lithium salt, and the mass proportion of the fluorine-containing lithium salt is recorded as N% based on the total mass of the electrolyte;

[0008] Z, E and N satisfy: 0.2≤(E+N) / Z≤10.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] (1) The lithium-ion secondary battery provided by the present invention can improve the high-temperature storage performance and low-temperature cycle performance of the battery by adjusting the magnesium content Z in the silicon-carbon material, the mass percentage E% of the cyclic carbonate, and the mass percentage N% of the fluorine-containing lithium salt, when Z, E, and N satisfy a specific relationship;

[0011] (2) The lithium-ion secondary battery provided by the present invention can further improve the adhesion between the diaphragm and the electrode, and enhance the high-temperature storage stability of the battery by further adjusting the area G of the termination tape.

[0012] (3) The lithium-ion secondary battery provided by the present invention can further improve the battery's anti-drop performance by further adding a magnesium-containing additive to the electrolyte.

[0013] (4) The lithium-ion secondary battery provided by the present invention can further improve the stability of the interface film and enhance the cycle stability of the battery by further adding nitrile additives, cyclic sulfonate additives and fluorinated cyclic carbonate additives to the electrolyte.

[0014] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Shown is a schematic cross-section of the core.

[0016] Figure 2 Shown is a schematic diagram of the surfaces of the positive electrode sheet on both sides.

[0017] Figure numerals: 1-terminal tape; 2-positive electrode current collector; 3-positive electrode active material; 4-negative electrode current collector; 5-negative electrode active material; 6-separator; 7-positive electrode sheet; 8-negative electrode sheet; 9-double-sided area; 10-single-sided area; 11-empty foil area. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0020] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0021] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0022] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material; the silicon-carbon material comprises a Mg element, and the content of the Mg element is recorded as Zppm;

[0023] The electrolyte includes a first solvent, and the first solvent includes a cyclic carbonate; the mass proportion of the cyclic carbonate is recorded as E% based on the total mass of the electrolyte;

[0024] The electrolyte includes a fluorine-containing lithium salt, and the mass proportion of the fluorine-containing lithium salt is recorded as N% based on the total mass of the electrolyte;

[0025] Z, E and N satisfy: 0.2≤(E+N) / Z≤10.

[0026] Exemplarily, the value of (E+N) / Z can be, for example, 0.2, 0.3, 0.4, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any point value in the range consisting of any two of the above point values.

[0027] The present invention has found that when magnesium is doped into silicon-carbon material and an electrolyte including fluorine-containing lithium salt and cyclic carbonate is used in combination, the interaction between magnesium ions and anions is greater than the solvation between magnesium ions and cyclic carbonate, which is conducive to the formation of a fluorine-containing and firm SEI film mainly composed of MgF, which has higher stability than a conventional SEI film, improves the strength of the SEI film, inhibits the volume expansion of the silicon-containing negative electrode, reduces the pulverization and shedding of the negative electrode particles, and improves the cycle performance of the battery; and the cyclic carbonate, as a film-forming solvent, can form a stable SEI film on the surface of the negative electrode, inhibits the side reactions of other components in the electrolyte at the negative electrode interface, and reduces the damage and cracking of the SEI film caused by the expansion of the silicon-containing negative electrode, thereby reducing the continuous and excessive decomposition of the cyclic carbonate and other components of the electrolyte on the exposed SEI film surface, improving the problem of low conductivity of the silicon-carbon negative electrode, and can effectively inhibit the high-temperature decomposition and gas production of the negative electrode interface components, and can also improve the high-temperature storage performance and low-temperature cycle performance of the battery.

[0028] At the same time, by adjusting the relationship among the magnesium content Z, the mass proportion E of the cyclic carbonate and the mass proportion N of the fluorine-containing lithium salt to satisfy 0.2≤(E+N) / Z≤10, it is possible to prevent severe high-temperature gas production caused by excessive content of cyclic carbonate and fluorine-containing lithium salt, and avoid excessive magnesium content causing poor high-temperature stability of silicon-carbon materials, thereby affecting the high-temperature performance of the battery.

[0029] In some embodiments, Z, E and N satisfy: 0.3≤(E+N) / Z≤5; adjusting Z, E and N to further satisfy the above range can form a more stable SEI film, further improving the high temperature storage and low temperature cycle of the battery.

[0030] In some embodiments, the content Z of magnesium element satisfies: 5≤Z≤200, and the content of magnesium element can be, for example, 5ppm, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 110ppm, 120ppm, 130ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm, 200ppm or any point value in the range composed of any two of the above point values, preferably 10≤Z≤100. When the content of magnesium element satisfies the above range, it can avoid that the content of magnesium element in the silicon-carbon material is too high when Z>200, and the reaction of magnesium with electrolyte or other components under high temperature conditions generates more heat and gas to affect the high temperature performance of the battery, and reduce the internal resistance of the battery; when Z<5, the content of magnesium element is too low, the stability of SEI film is not significantly improved, and the volume expansion of silicon-containing negative electrode cannot be effectively inhibited.

[0031] Exemplarily, the content of magnesium in the silicon-carbon material is detected by ICP.

[0032] In some embodiments, the cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, and butylene carbonate, preferably ethylene carbonate EC. Part of EC coordinates with transition metal ions through oxygen-containing groups to reduce the deposition of transition metal ions on the negative electrode surface causing interfacial side reactions. The uncoordinated EC is free in the electrolyte structure, which can also improve the wettability of the electrolyte and improve the problem of low conductivity of the silicon-carbon negative electrode.

[0033] In some embodiments, the mass proportion E of the cyclic carbonate satisfies: 2≤E≤30, and the mass proportion of the cyclic carbonate can be, for example, 2%, 4%, 6%, 8%, 10%, 15%, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range of the above two point values, preferably 5≤E≤25. When the mass proportion of the cyclic carbonate further satisfies the above range, it can be avoided that when E<2%, the cyclic carbonate content is too low to form an SEI film on the negative electrode surface, which reduces the battery cycle stability and increases the high temperature storage and safety risks; when E>30%, excessive cyclic carbonate increases the viscosity of the electrolyte, which is not conducive to the penetration of the electrolyte into the pole piece, and at the same time makes the SEI film formed on the negative electrode surface too thick, increases the interface impedance, and is not conducive to lithium ion transmission.

[0034] In some embodiments, the mass proportion N of the fluorine-containing lithium salt satisfies: 10≤N≤30, and the mass proportion of the fluorine-containing lithium salt can be, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range composed of any two of the above point values, preferably 14≤N≤25; preferably, the fluorine-containing lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), and lithium tetrafluoroborate. When the mass proportion of fluorine-containing lithium salt further meets the above range, it can be avoided that when N is less than 10%, the content of fluorine-containing lithium salt in the electrolyte is too low, and after the battery cycle process consumes lithium ions to form SEI film, insufficient active lithium in the electrolyte in the later stage of the cycle and poor battery cycle stability; when N is greater than 30%, the content of fluorine-containing lithium salt is too high, resulting in increased viscosity of the electrolyte, which is not conducive to the penetration of the electrolyte and the rapid transmission of ions in the electrolyte. At the same time, excessive fluorine-containing lithium salt decomposes to generate heat, increasing the safety risk of the battery.

[0035] In some embodiments, the silicon-carbon material further comprises at least one of the metal elements Na, K, Ca, Fe, Cr, Ni, and Cu; the total content of the metal elements is 100ppm-500ppm, for example, 100ppm, 200ppm, 300ppm, 400ppm, and 500ppm. When the silicon-carbon material is further doped with the above metal elements and the total content of the metal elements is controlled within the above range, the elemental composition and surface activity of the carbon material can be changed, the carrier concentration in the silicon-carbon material can be increased, the resistivity can be reduced, and the conductivity can be improved.

[0036] For example, the contents of metal elements such as Na, K, Ca, Fe, Cr, Ni, and Cu in silicon-carbon materials can be detected by ICP.

[0037] In some embodiments, the silicon-carbon material further includes at least one of the non-metallic elements S and O; the total content of the non-metallic elements is recorded as 10ppm-100ppm, for example, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm. When the silicon-carbon material is further doped with the non-metallic elements S and / or O, and the total content of the non-metallic elements is controlled within the above range, the stability of the silicon-carbon material can be improved and the side reaction between the silicon-carbon material and the electrolyte can be reduced.

[0038] In some embodiments, the silicon-carbon material includes an O element, and the content of the O element is 50ppm-10000ppm, for example, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 500ppm, 1000ppm, 5000ppm, 10000ppm. Oxygen doping of the silicon-carbon material can improve the chemical stability of the material and prevent it from reacting with oxygen, water, etc. in the surrounding environment.

[0039] For example, in silicon-carbon materials, non-metallic elements such as O and S can be detected by an organic element analyzer.

[0040] In some embodiments, in the silicon-carbon material, the total content of metal elements and non-metal elements is 100ppm-20000ppm, for example, it can be 100ppm, 200ppm, 500ppm, 1000ppm, 2000ppm, 5000ppm, 10000ppm, 15000ppm, 20000ppm. Wherein, the non-metal elements do not include silicon and carbon. When the total content of metal elements and non-metal elements is adjusted within the above range, it can be avoided that the total content of metal elements and non-metal elements is too high to affect the stability and electrochemical properties of the silicon-carbon material; it can be avoided that the total content of metal elements and non-metal elements is too low, and the conductivity and stability of the silicon-carbon material are not significantly improved.

[0041] In some embodiments, the sphericity of the silicon-carbon material is recorded as B, and B satisfies 0.5≤B≤1. The sphericity of the silicon-carbon material can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any point value in the range of the above two point values. When the sphericity of the silicon-carbon material further satisfies the above range, it can be avoided that when B is less than 0.5, the silicon-carbon material particles have poor flow properties, which affects the homogenization operation in the battery manufacturing process, and is also easy to cause uneven coating of the negative electrode slurry during the coating process, affecting the stability of the negative electrode and causing poor drop performance.

[0042] In some embodiments, the mass percentage of silicon in the negative electrode active material is 3%-60%, for example, it can be 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any point value in the range of any two of the above points, preferably 5%-50%. When the mass percentage of silicon further meets the above range, it can improve the energy density of the battery while preventing the problem of excessive volume expansion of the silicon-containing negative electrode caused by silicon-carbon materials.

[0043] Exemplarily, the mass proportion of silicon in the negative electrode active material can be obtained by acid-treating the negative electrode active material and then performing ICP analysis. Alternatively, the test method for the mass proportion of silicon can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions are: sample size 5 mg, air as atmosphere, heating rate 10°C / min from room temperature to 900°C and constant temperature for 40 minutes. The relationship between the mass proportion of silicon-carbon material (x) and the final weight residual percentage (y) of the entire test is: x=7y / 15.

[0044] In some embodiments, the Dv50 of the silicon-carbon material is 5μm-15μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any point value in the range composed of two points above. When the Dv50 of the silicon-carbon material further meets the above range, the expansion of the silicon-containing negative electrode can be further suppressed, and the high temperature storage performance and low temperature cycle performance of the battery can be improved. In some embodiments, the negative electrode active material also includes a carbon material, and the carbon material includes one or more of artificial graphite, natural graphite, hard carbon, and soft carbon.

[0045] Due to the volume expansion of the negative electrode silicon-carbon material and the gas production of the battery, the battery structure is unstable, and the diaphragm and the electrode sheet are easily separated. The present invention further proposes: the battery also includes a diaphragm, the positive electrode sheet, the diaphragm and the negative electrode sheet are stacked in sequence and wound from one end along the length direction to form a winding core; the positive electrode sheet is provided with a termination tape at the tail of the winding direction; the positive electrode sheet includes a positive electrode collector, and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector; the termination tape includes a first area and a second area, the first area covers the positive electrode active material layer, and the second area covers the positive electrode collector; the termination tape arranged along the tail of the positive electrode sheet in the winding direction can prevent burrs from piercing the diaphragm and avoiding its contact with the positive electrode sheet, avoiding the expansion of the silicon-carbon material or the gas production of the battery in a high-temperature fully charged state. The unstable battery structure is avoided, the structural stability of the battery is improved, the risk of battery short circuit is reduced, and the safety performance and high-temperature storage stability of the battery are improved.

[0046] In some embodiments, Figure 1 As shown, the positive electrode sheet 7, the separator 6 and the negative electrode sheet 8 are stacked in sequence and wound from one end along the length direction (the direction of the arrow in the figure) to form a winding core, and the terminating tape 1 is arranged at the tail of the positive electrode sheet in the winding direction.

[0047] In some embodiments, Figure 2 As shown, the termination tape 1 is located on two opposite surfaces of the positive electrode sheet 7, namely the long side and the short side of the positive electrode sheet 7, combined with Figure 1 , the long side of the positive electrode sheet 7 is located on the inner side of the winding core, and the short side of the positive electrode sheet 7 is located on the outer side of the winding core. The long side of the positive electrode sheet 7 includes a double-sided area 9, a single-sided area 10 and an empty foil area 11. The double-sided area 9 indicates that the opposite sides of the positive electrode sheet are coated with a positive electrode active material layer; the single-sided area 10 indicates that only one side of the positive electrode sheet is coated with a positive electrode active material layer; the empty foil area 11 indicates that neither side of the positive electrode sheet is coated with a positive electrode active material layer. The long side of the positive electrode sheet 7 includes a double-sided area 9, a single-sided area 10 and an empty foil area 11, and the termination tape 1 is pasted at the junction of the single-sided area 10 and the empty foil area 11; the short side of the positive electrode sheet 7 includes a double-sided area 9 and an empty foil area 11, and the termination tape 1 is pasted at the junction of the double-sided area 9 and the empty foil area 11; combined with the attached Figure 2 The length of the termination tape refers to the dimension along the width direction of the positive electrode sheet, and the width of the termination tape refers to the dimension along the length direction of the positive electrode sheet.

[0048] In some embodiments, the length of the termination tape is ≥ the width of the positive electrode sheet, ensuring that the tape can completely cover the positive electrode sheet in each batch of positive electrode sheets, avoiding the impact of process fluctuations, effectively preventing burrs from piercing the diaphragm and causing thermal runaway, and further improving the safety performance and high-temperature storage stability of the battery.

[0049] In some embodiments, the stop tape area is denoted as G mm 2 , G satisfies: 120≤G≤8000, the length-to-width ratio of the termination tape can be, for example, 120 mm 2 , 200mm 2 、300mm 2 , 500mm 2 , 800mm 2 , 1000mm 2 、3000mm 2 , 5000mm 2 , 8000mm 2Or any point value in the range formed by the above two point values. When the area of ​​the termination tape is adjusted to further meet the above range, it can be avoided that when G is less than 120, the area of ​​the termination tape is too small, and it cannot effectively protect the edge of the positive electrode sheet, resulting in direct contact between the positive electrode and the negative electrode and causing a short circuit; it can also be avoided that when G is greater than 8000, the area of ​​the termination tape is too large, which limits the expansion space of the silicon negative electrode, is not conducive to the diffusion of the volume expansion stress of the silicon-carbon negative electrode, and causes the electrode sheet to wrinkle, thereby affecting the cycle performance and stability of the battery.

[0050] In the present invention, the length and width of the termination tape are not specifically limited, and can be adaptively adjusted according to the size of the positive electrode sheet. Exemplarily, the width of the termination tape can be 5mm-50mm, for example, it can be 5mm, 10mm, 20mm, 30mm, 40mm, 50mm or any point value between the ranges composed of the above two point values, preferably 5-30mm. Exemplarily, the length of the termination tape can be 25mm-150mm, for example, it can be 25mm, 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm or any point value between the ranges composed of the above two point values.

[0051] In the present invention, the type of the termination tape is not specifically limited, for example, it can be selected from at least one of masking tape, fiber tape, PACK high temperature tape, PET tape, and acrylic tape. The commonly used insulating tape in this field can be divided into tape with a release layer and tape without a release layer. The above-mentioned different types of tapes can be prepared as tape with a release layer (the general structure is substrate + adhesive layer + release layer, such as double-sided tape, with a double-sided bonding function), or tape without a release layer (the general structure is substrate + adhesive layer, such as ordinary single-sided tape, with a single-sided bonding function), preferably tape without a release layer.

[0052] In some embodiments, the electrolyte may further include a magnesium-containing additive; preferably, the magnesium-containing additive includes one or more of magnesium bis(trifluoromethylsulfonyl)imide, magnesium hexafluorophosphate, magnesium difluorophosphate, magnesium bis(trifluoromethylsulfonyl)imide, magnesium bis(trifluoromethylsulfonyl)imide, and magnesium tetrafluoroborate; based on the total mass of the electrolyte, the mass proportion of the magnesium-containing additive is 0.1%-3%, and the mass proportion of the magnesium-containing additive can be, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3% or any point value in the range composed of any two of the above point values. When the mass proportion of the magnesium-containing additive further meets the above range, the magnesium-containing additive can adsorb more cyclic carbonates to coordinate with magnesium ions, reduce the coordination solvent of lithium ions, increase the migration rate of lithium ions, and prevent interfacial lithium precipitation due to poor lithium ion kinetics; during the charging process, lithium ions, magnesium ions and silicon carbon are alloyed to form magnesium alloy-coated silicon particles, which improves the surface flexibility of silicon particles and prevents silicon-carbon particles from breaking and detaching, thereby avoiding local silicon-carbon particles from piercing the diaphragm when falling and causing battery short circuit, further improving the battery's drop resistance and improving battery safety.

[0053] In some embodiments, the electrolyte further comprises a combination of one or more of a nitrile additive, a cyclic sulfonate additive and a fluorinated cyclic carbonate additive, preferably a combination of a nitrile additive, a cyclic sulfonate additive and a fluorinated cyclic carbonate additive.

[0054] In some embodiments, the nitrile additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexane trinitrile, glutaronitrile, 1,2,3-tris(2-cyanoethoxy)propane and 1,2,3,4,5,6-(2-cyanoethoxy)hexane; based on the total mass of the electrolyte, the mass proportion of the nitrile additive is 2%-6%, and the mass proportion of the nitrile additive can be, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any point value in the range of the above two point values. Nitrile additives can complex positive electrode metal ions, improve the stability of positive electrode materials, and further improve battery cycle stability.

[0055] In some embodiments, the cyclic sulfonate additive includes at least one of 1,3-propane sulfonate, propylene-1,3 sulfonate, vinyl sulfite, vinyl sulfate, and methylene disulfonate; based on the total mass of the electrolyte, the mass proportion of the cyclic sulfonate additive is 1%-5%, and the mass proportion of the cyclic sulfonate additive can be, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any point value in the range of the above two point values. The cyclic sulfonate additive can improve the ion conductivity of the CEI membrane, improve the performance of the interface membrane, and further improve the battery cycle stability.

[0056] In some embodiments, the fluorinated cyclic carbonate additive includes at least one of fluoroethylene carbonate and difluoroethylene carbonate; based on the total mass of the electrolyte, the mass proportion of the fluorinated cyclic carbonate additive is 5%-15%, and the mass proportion of the fluorinated cyclic carbonate additive can be, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any point value in the range of the above two point values. Fluorinated cyclic carbonate additives can improve the strength of SEI film / CEI film, improve the performance of the interface film, and further improve the battery cycle stability.

[0057] In some embodiments, the electrolyte further includes a second solvent, which includes a carboxylate solvent, and the carboxylate solvent includes one or more of ethyl propionate, ethyl acetate, propyl propionate, methyl acetate, and methyl propionate. The carboxylate solvent increases the solubility of the lithium salt, maintains the stability of each component in the electrolyte, and further improves the battery cycle stability.

[0058] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0060] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0061] Example 1-1

[0062] (1) Preparation of positive electrode

[0063] Lithium cobalt oxide, binder polyvinylidene fluoride (PVDF 500), and conductive carbon black (Super P; carbon nanotubes = 2:1) were mixed in N-methylpyrrolidone (NMP) solvent at a weight ratio of 97.5:2:2.5, and stirred continuously in a stirrer to form a uniform, flowing positive electrode slurry. Subsequently, the positive electrode slurry was coated on an aluminum foil with a thickness of 10 μm, sent to a 120°C vacuum oven for drying for 6 hours, and then rolled and cut to obtain the desired positive electrode sheet.

[0064] (2) Negative electrode preparation

[0065] Graphite, silicon-carbon material, conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber were mixed in a water solvent at a weight ratio of 91:7:1:0.5:0.5, and stirred continuously in a stirrer to form a uniform, flowing negative electrode slurry. Subsequently, the slurry was coated on the surface of a 10μm thick current collector copper foil, dried in a 120℃ vacuum oven for 6h, and then rolled and cut to obtain the desired negative electrode sheet.

[0066] (3) Preparation of electrolyte

[0067] In a glove box filled with argon (water <1ppm, oxygen <1ppm), ethylene carbonate, propylene carbonate, propyl propionate, and ethyl propionate solvents are mixed into a uniform solvent, and LiPF6, 2% 1,3-propane sultone, 3% 1,3,6-hexane trinitrile, 10% fluoroethylene carbonate, and 1.5% magnesium bis(fluorosulfonyl)imide, which account for 15.5% of the total mass of the electrolyte, are slowly added. After stirring evenly, the desired lithium-ion battery electrolyte is obtained. Based on the total mass of the electrolyte, the mass proportion of cyclic carbonate is 25% (of which the mass proportion of ethylene carbonate is 12.5%, and the mass proportion of propylene carbonate is 12.5%). The total amount of propyl propionate and ethyl propionate can be calculated, and the mass ratio of the two is 5:2.

[0068] (4) Preparation of diaphragm

[0069] A 2μm polyvinylidene fluoride layer is coated on one side of a 6μm polyethylene substrate; a 1μm mixed layer of polyvinylidene fluoride and alumina (the mass ratio of polyvinylidene fluoride to alumina is 5:95) is coated on one side, and then a 2μm polyvinylidene fluoride layer is coated, which are used to contact the negative and positive electrodes respectively.

[0070] (5) Preparation of lithium-ion batteries

[0071] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to prepare a bare cell, which is then placed in an aluminum-plastic film. The prepared electrolyte is injected into the dried bare cell, and the desired lithium-ion battery is obtained through vacuum packaging, room temperature standing, high-temperature formation and other processes.

[0072] (6) Battery performance test

[0073] (i) Low temperature cycle test

[0074] The batteries obtained in the above examples and comparative examples were placed in a low temperature test box (0±2)°C, and charged to 4.4V (cut-off current was 0.05C) at a current density of 1.2C. After the battery was fully charged, it was left for 5 minutes, and then discharged at a current density of 0.5C (cut-off voltage 3.0V). The discharge capacity was recorded as the initial capacity Q1. When the cycle reached 200 cycles, the last discharge capacity Q2 of the battery was recorded. Capacity retention rate (%) = Q2 / Q1×100%

[0075] (ii) High temperature storage test

[0076] The batteries obtained in the above examples and comparative examples were fully charged at an ambient temperature of (25±2)°C (testing the initial thickness of the battery), charged at 0.7C to the upper limit voltage (the cut-off current was 0.05C), and stored at 70°C±2°C until the thickness expansion was greater than 20%, and then the test was stopped (process data was measured once a day: the hot thickness was tested immediately after the sample was taken out), and the storage time was recorded.

[0077] (iii) Drop test

[0078] The batteries obtained in the above embodiments and comparative examples were fully charged at an ambient temperature of (25±2)°C, and the battery cells were dropped onto a concrete floor from a height of 1m, with 6 faces and 4 corners dropped once each. During the test, a directional drop was performed with a clamping arm. When the battery did not catch fire, explode, or emit smoke, it was recorded as passed.

[0079] (iv) DC internal resistance test experiment

[0080] The DC internal resistance test of the batteries obtained in the above embodiments and comparative examples was performed using a DC load meter. The batteries obtained in the above embodiments and comparative examples were fully charged at an ambient temperature of (25±2)°C, with the current set to 1A and the duration set to 500ms, and the DC internal resistance of the fully charged batteries was measured.

[0081] (v) Adhesion test

[0082] The adhesive tape is attached to the electrode. One end of the adhesive tape of the above embodiment and comparative example is fixed to one end of the tensile machine, and the electrode is fixed to the other end of the tensile machine. The machine is started to continuously stretch at 100 mm / min, and the bonding force is recorded.

[0083] The examples 1 to 3, and comparative examples 1 to 4 were carried out with reference to the examples 1 to 1, and the main differences are shown in Table 1. In the example 1 group, the magnesium content Z was changed; the cyclic carbonate content E was changed in the example 2 group; the fluorine-containing lithium salt content N was changed in the example 3 group; the magnesium content Z was changed in comparative examples 1 and 2; the magnesium content Z and the cyclic carbonate content E were changed in comparative example 3; the magnesium content Z, the cyclic carbonate content E and the fluorine-containing lithium salt content N were changed in comparative example 4.

[0084] Table 1

[0085]

[0086]

[0087] It can be seen from Table 1 that when the relationship among the content Z of magnesium element, the mass proportion E of cyclic carbonate and the mass proportion N of fluorine-containing lithium salt satisfies 0.2≤(E+N) / Z≤10, the low-temperature cycle performance and high-temperature storage performance of the battery can be improved, and the internal resistance can be reduced.

[0088] In Example 4-5, the tape was applied with reference to Example 1-1. Compared with Example 1-1, tape was applied to the winding tail of the positive electrode sheet. The specific operation steps were as follows: the bare cell was transferred to the glue sticking machine, the tape was evenly arranged and attached to a fixed position using a glue dispensing machine, and the tape was precisely cut with a cutting knife to complete the glue sticking process. The area G of the tape was changed in Example 4, and the sphericity B of the silicon-carbon material was changed in Example 5, as shown in Table 2. When G=5000, the tape length was 500mm and the width was 10mm, and G was adjusted by changing the width.

[0089] Table 2

[0090]

[0091]

[0092] It can be seen from Table 2 that when adhesive tape is attached to the tail of the positive electrode sheet and the area G of the adhesive tape is within the protection scope of the present invention, the low-temperature cycle performance and high-temperature storage performance of the battery can be improved, and the internal resistance can be reduced. The sphericity B of the silicon-carbon material is within the protection scope of the present invention, which can improve the anti-drop performance of the battery.

[0093] The Example 6-9 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. Among them, the content of the nitrile additive was changed in the Example 6 group; the content of the cyclic sulfonate was changed in the Example 7 group; the content of the fluorinated cyclic carbonate was changed in the Example 8 group; and the content of the magnesium-containing additive was changed in the Example 9 group.

[0094] Table 3

[0095]

[0096]

[0097] It can be seen from Table 3 that adding nitrile additives, cyclic sulfonates, fluorinated cyclic carbonates and magnesium-containing additives to the electrolyte can improve the low-temperature cycle performance, high-temperature storage performance and drop resistance of the battery.

[0098] Example 10 group was carried out with reference to Example 1-1, and the silicon content in the negative electrode active material was changed by adjusting the mass of the silicon-carbon material. The specific differences are shown in Table 4.

[0099] Table 4

[0100]

[0101] It can be seen from Table 4 that the greater the silicon content, the greater the internal resistance of the battery. When the silicon content is within the protection scope of the present invention, the high temperature performance of the battery can be improved.

[0102] Example 11-12 was carried out with reference to Example 1-1, except that the type and content of the metal elements doped in the silicon-carbon material were changed in Example 11; the type and content of the non-metallic elements doped in the silicon-carbon material were changed in Example 12. The specific differences are shown in Table 5.

[0103] Table 5

[0104]

[0105] It can be seen from Table 5 that the non-metallic elements S and / or O in the silicon-carbon material can improve the stability of the silicon-carbon material, help improve the low-temperature cycle performance and high-temperature storage performance of the battery, and reduce the internal resistance of the battery.

[0106] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material; the silicon-carbon material comprises a Mg element, and the content of the Mg element is recorded as Zppm; The electrolyte includes a first solvent, and the first solvent includes a cyclic carbonate; the mass proportion of the cyclic carbonate is recorded as E% based on the total mass of the electrolyte; The electrolyte includes a fluorine-containing lithium salt, and the mass proportion of the fluorine-containing lithium salt is recorded as N% based on the total mass of the electrolyte; Z, E and N satisfy: 0.2≤(E+N) / Z≤10.

2. The battery according to claim 1, characterized in that Z, E and N satisfy: 0.3≤(E+N) / Z≤5; and / or, Z satisfies: 5≤Z≤200, preferably 10≤Z≤100; And / or, E satisfies: 2≤E≤30, preferably 5≤E≤25; And / or, N satisfies: 10≤N≤30, preferably 14≤N≤25.

3. The battery according to claim 1, characterized in that The silicon-carbon material further comprises at least one of the metal elements Na, K, Ca, Fe, Cr, Ni, and Cu; the total content of the metal elements is 100ppm-500ppm; Preferably, the silicon-carbon material further comprises at least one of non-metallic elements S and O; the total content of the non-metallic elements is recorded as 10ppm-100ppm; Preferably, the silicon-carbon material includes O element, and the content of O element is 50ppm-10000ppm.

4. The battery according to claim 1, characterized in that In the negative electrode active material, the mass proportion of silicon element is 3%-60%, preferably 5%-50%; Preferably, the negative electrode active material further comprises a carbon material, and the carbon material comprises one or more of artificial graphite, natural graphite, hard carbon and soft carbon.

5. The battery according to claim 1, characterized in that The sphericity of the silicon-carbon material is denoted as B, where B satisfies 0.5≤B≤1; Preferably, the Dv50 of the silicon-carbon material is 5 μm-15 μm.

6. The battery according to claim 5, characterized in that The battery further comprises a separator, wherein the positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and wound from one end along the length direction to form a winding core; a stop tape is provided at the tail of the positive electrode sheet in the winding direction; The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector; the termination tape includes a first area and a second area, the first area covers the positive electrode active material layer, and the second area covers the positive electrode current collector; the area of ​​the termination tape is recorded as Gmm 2 , G satisfies: 120≤G≤8000; Preferably, the length of the termination tape is greater than or equal to the width of the positive electrode sheet.

7. The battery according to any one of claims 1 to 6, characterized in that: The electrolyte includes a magnesium-containing additive; Preferably, the magnesium-containing additive includes one or more of magnesium bis(trifluoromethylsulfonyl)imide, magnesium hexafluorophosphate, magnesium difluorophosphate, magnesium bis(trifluoromethylsulfonyl)imide, magnesium bis(trifluoromethylsulfonyl)imide, and magnesium tetrafluoroborate; Preferably, based on the total mass of the electrolyte, the mass proportion of the magnesium-containing additive is 0.1%-3%.

8. The battery according to any one of claims 1 to 6, characterized in that: The cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, and butylene carbonate, preferably ethylene carbonate; Preferably, the electrolyte further comprises a second solvent, the second solvent comprises a carboxylate solvent, and the carboxylate solvent comprises one or more of ethyl propionate, ethyl acetate, propyl propionate, methyl acetate, and methyl propionate; Preferably, the fluorine-containing lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium tetrafluoroborate.

9. The battery according to any one of claims 1 to 6, characterized in that: The electrolyte further comprises a combination of one or more of a nitrile additive, a cyclic sulfonate additive and a fluorinated cyclic carbonate additive; Preferably, based on the total mass of the electrolyte, the mass proportion of the nitrile additive is 2%-6%; Preferably, based on the total mass of the electrolyte, the mass proportion of the cyclic sulfonate additive is 1%-5%; Preferably, based on the total mass of the electrolyte, the mass proportion of the fluorinated cyclic carbonate additive is 5%-15%.

10. The battery according to claim 9, characterized in that The nitrile additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, 1,2,3-tris(2-cyanoethoxy)propane and 1,2,3,4,5,6-(2-cyanoethoxy)hexane; And / or, the cyclic sulfonate additive includes at least one of 1,3-propane sulfonate, propylene-1,3 sulfonate, vinyl sulfite, vinyl sulfate, and methylene methane disulfonate; And / or, the fluorinated cyclic carbonate additive includes at least one of fluoroethylene carbonate and bisfluoroethylene carbonate.